2008
DOI: 10.1128/iai.00758-07
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Efflux Pump TolC Promotes Aggregation of Enteroaggregative E. coli 042

Abstract: Enteroaggregative Escherichia coli (EAEC) is an emerging enteric pathogen in both developing and industrialized countries. EAEC is defined as a diarrheal pathogen based on its characteristic aggregative adherence to HEp-2 cells in culture and its biofilm formation on the intestinal mucosa. We have reported that the novel protein AatA, which is encoded on the EAEC virulence plasmid pAA2, localizes to the outer membrane and facilitates export of the dispersin Aap across the outer membrane. Because AatA is an E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…6A). TolC has been reported to be required for adhesion and biofilm formation in pathogenic enteroaggregative E. coli; deletion mutants have decreased aggregation and adhesion under growth conditions with high-glucose Dulbecco's minimal medium (65,66), consistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…6A). TolC has been reported to be required for adhesion and biofilm formation in pathogenic enteroaggregative E. coli; deletion mutants have decreased aggregation and adhesion under growth conditions with high-glucose Dulbecco's minimal medium (65,66), consistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have shown that the novel protein aatA, which is encoded on EAEC virulence plasmid pAA2, localizes to the outer membrane of this bacterium and facilitates export of the dispersin aap across the outer membrane. 45,46 Our results may support this notion because aatA and aap were detected in greater than 68% of patients with diarrhea. Further study is required for a firm conclusion.…”
supporting
confidence: 80%
“…PA␤N in combination with an iron chelator showed synergistic activity against P. aeruginosa biofilm development (890). Similar to the role of TolC, a plasmid encoding a TolC homolog, AatA, promoted aggregation and biofilm formation of an enteroaggregative E. coli isolate (891). A large conjugative plasmid encoding the OqxAB pump and type 3 fimbriae enabled E. coli to form a biofilm (892).…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 98%